ChemInform Abstract: Directly Regioselective Protection of Secondary Hydroxyl Group on Ribosides in Aqueous Solution. Issue 47 (4th November 2013) - Xu, Ruigang; Liu, Fei; Liu, Yingju; Chen, Beiqing; Liu, Feng‐Wu
Abstract The treatment with benzoyl chloride and Na2CO3 in aqueous acetonitrile allows regioselective benzoylation of secondary hydroxyl moieties in ribosides.